Immune Response to Sports - Widiastuti, Ida Ayu Eka (Faculty of Medicine Universitas Mataram, 2020)
The physiological function of the immune system is to defend against infectious microbes; even non-infectious foreign substances and damaged cell products that can elicit an immune response. The response from exercise, both acute and chronic, will have an effect on the components of the immune system. The immune response that occurs depends on the intensity and duration of exercise. Moderate intensity exercise will stimulate various parameters related to cellular immunity so that it can reduce the risk of infection, while high intensity exercise will result in a reduction in the same parameters, which will increase the risk of infectious diseases. The response from exercise or doing regular physical activity can affect immune cells, such as: neutrophils, antigen precenting cells (APC), natural killer cells (NK cells), and lymphocytes as well as cytokine production.